Pengaruh Penerapan Digital Payment & Digital Marketing Terhadap Peningkatan Pendapatan UMKM (Studi Pada UMKM Binaan Bank Indonesia Di Kota Gorontalo): (Studi pada UMKM Binaan Bank Indonesia di Kota Gorontalo) - Nur Syafira Aulia Fatihah; Muliyani Mahmud; Nurharyati Panigoro (Al-Buhuts, 2024)
This research aims to find out the effect of implementing digital payments and digital marketing on increasing MSME income in MSMEs assisted by Bank Indonesia in Gorontalo City. This type of research uses a quantitative approach. The population in this research is MSMEs assisted by Bank Indonesia in Gorontalo City, namely 45 MSMEs. This research uses primary data obtained directly from respondents. The population in this study was 45 MSMEs assisted by Bank Indonesia in Gorontalo City, with the criteria that will later be used as respondents, namely 2 people per MSME. Meanwhile, sampling used the Non Probability Sampling Technique with the Purposive Sampling type. The results of this research are that digital payments have no effect on increasing MSME income, while digital marketing has an effect on increasing MSME income, especially MSMEs assisted by Bank Indonesia in Gorontalo City.